Impact of sensing vector on insertable cardiac monitor detection of P and R wave amplitude. (25th November 2020) - Pitman, B.M; Tarone, R; Jones, E; Kadhim, K; Linz, D; Roberts-Thomson, K; Young, G.D; Mariani, J; Wong, C.X; Sanders, P; Lau, D.H
Abstract: Background: P-wave visibility is useful for diagnosis of atrial arrhythmias via insertable cardiac monitors (ICM). Purpose: To compare the sensing capability of ICM with different vector length: Medtronic REVEAL LINQ (45mm) vs. Biotronik Biomonitor BMIII (75mm). Methods: We accessed de-identified remote monitoring transmissions from n=40 patients with BMIII from Biotronik for comparison with n=80 gender- and body mass index (BMI)-matched patients with REVEAL LINQ. Digital measurement of calibrated ICM electrograms was performed using DigitizeIt© (V2.3.3, Germany) of 5 consecutive P-QRS complexes by 3 investigators independently. P-wave amplitude was measured from baseline to peak and R-wave amplitude was measured from peak-to-peak. Further, we evaluated the impact of BMI on P-wave visibility. Results: Patients in both groups are well matched for gender and BMI (53% male, mean BMI 26.7 kg/m 2 ; both p=NS). P-wave and R-wave amplitude were 89% & 20% larger in the BMIII vs. LINQ (0.072±0.039 vs. 0.038±0.022mV, p=0.0001; & 0.83±0.42 vs. 0.69±0.45mV, p=0.095 respectively; Figure). Consequently, the P/R-wave ratio was 44% greater for the BMIII (p=0.002). Multivariate regression analysis showed that increasing BMI, female gender and LINQ were independently associated with lower P-wave amplitude (all P<0.001). Inter-operator reproducibility of P-wave measures was very good (ICC 0.91, P<0.001). Conclusion: The longer ICM sensing vector of BMIII yielded considerable larger P-wave amplitude than LINQ, that was not impacted by increasing BMI. Better P-wave visibility may improve clinical decision-making after device-detected arrhythmias while further studies are needed to determine its impact on clinical outcomes. Funding Acknowledgement: Type of funding source: None